2015
DOI: 10.3389/fenvs.2015.00060
|View full text |Cite
|
Sign up to set email alerts
|

El Niño-southern oscillations and lathyrism epidemics

Abstract: Epidemics of lathyrism, a neurological syndrome of spastic paraparesis, have occurred during severe droughts in Europe, Asia, and Africa for millenia. Causation is linked to exposure to β-N-oxalyl-L-α,β-diaminopropionic acid (β-L-ODAP), a neurotoxin in Lathyrus sativus. Lathyrism shares neurological features with konzo, a syndrome of predominantly spastic paraparesis which occurs during droughts in East and Central Africa and is linked to El Niño activity. This study was done to determine the relationship of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Wealth of household was not a significant factor to affect the intensity of land use for grass pea. Hillocks and Maruthi (2012) and Oluwole (2015) indicated that poor households opted grass pea production. However, our results revealed that household wealth was positively associated with decision of growing grass crop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wealth of household was not a significant factor to affect the intensity of land use for grass pea. Hillocks and Maruthi (2012) and Oluwole (2015) indicated that poor households opted grass pea production. However, our results revealed that household wealth was positively associated with decision of growing grass crop.…”
Section: Resultsmentioning
confidence: 99%
“…At a global scale, land put under grass pea production is estimated at about 1.5 million ha annually that produce about 1.2 million tons of the pulse, indicating the importance of the crop (Yang and Zhang, 2005;Siddique et al, 2006;Kumar et al, 2011). Thus, despite its severe consequences on human health, grass pea remains an important crop for some segments of people of many countries (Siddique et al, 1996;Siddique et al, 2006;Kumar et al, 2011;Singh et al, 2013;Oluwole, 2015) including in Ethiopia (Getahun et al, 1999;Tekle-Haimanot et al, 2005;Urga et al, 2005;Fikre et al, 2010;Damene, 2014). Lathyrism is a health problem in Ethiopian highlands with very high prevalence rates in the Amhara region (where grass pea is largely produced) (Getahun et al, 1999;Fikre et al, 2010;Woldeamanuel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%